Possible complications for the asplenic patient: a literature review (Research, Society and Development, 2022)
Introduction: The spleen is a lymphoid organ, which has filtration, hematological and immunological function. Therefore, the defense function in asplenic patients is reduced, making them more susceptible to severe infection. Objective: To understand the choice of surgical procedure, discuss the indication of splenectomy, identify prophylactic measures and report future complications. Methods: It has an exploratory qualitative character, based on an integrative literature review. Results and Discussion: Surgical indication may result from traumatic causes or not. According to the indications, it is possible to trace two different surgical techniques: and ssplenectomy by laparotomy and laparoscopic. Currently, it is known that asplenic patients have a depression in the immune system, with increased risk of sepsis and failure in antibiotic therapy, with rapid evolution to death and become susceptible to several infections caused by encapsulated germs. These germs are: Haemophilus influenzae type B Neisseria meningitidis (meningococcus) and Streptococcus pneumoniae. Vaccination against these pathogens prevents Fulminant Post-Splenectomy (IFPE) infection. Conclusion: The spleen is an important organ for immunity and even though it is not vital admits great consequences to the asplenic patient, with necessary interventions such as: vaccination, antibiotic therapy and health education, aiming to avoid a worse prognosis, reduce risks and morbidity and mortality. Through the study, sepsis and severe post-splenectomy infections were considered as the most severe situations. Therefore, it is of paramount importance to disseminate prophylactic methods, as well as the guidance of patients and their families on possible complications in order to avoid them.